Aligned Cycles in Thomas Adès's Piano Quintet. (9th October 2013) - Stoecker, Philip
Abstract In this article I investigate aligned cycles in Thomas Adès's Piano Quintet, Op. 20. First identified by Berg in a letter to Schoenberg and later discussed by George Perle and Dave Headlam, an aligned cycle is the result of two or more interval cycles unfolding in the same direction in a note‐against‐note alignment – for example, a rising whole‐tone scale (an interval‐2 cycle) simultaneously with a rising chromatic scale (an interval‐1 cycle). I begin by exploring in more detail the theoretical properties of three‐voice aligned cycles and use concentric circles to show how these cyclic structures generate a closed, tight‐knit family of harmonies. I then reveal how Adès uses aligned cycles to provide harmonic, melodic and motivic material throughout his Quintet. These cyclic structures are combined not only with other kinds of cycles (one‐, two‐ and five‐voice, and multi‐aggregate) but also with the non‐cyclic material in the piece. Finally, I discuss how all the transformations of the different cycles function within the large‐scale formal design of the piece.